Pemahaman Soft Skill untuk Anggota Koperasi BMT Bumi melalui Manajemen Pemasaran Syariah - Lindiawatie; Ria, Anita; Shahreza, Dhona (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
Public service aims to help the performance of the trade sector informal micro and small gathered in cooperative members Sharia BMT BUMI Cimanggis, Depok, through submission of an understanding of the importance of having a soft skills marketing management are realized in the form of a marketing strategy based on the Sharia. The method of implementation is done through a dialog approach to Islamic Cooperative Manager BMT BUMI intending to compile problem in General its profession as the perpetrator of the micro and small, then continued with the approach specifically through interactive dialogue direct settlement of related problems experienced by marketing management daily. A direct approach to finding a way out of the problem through interactive dialogue resulted in an understanding for partners about running a marketing strategy based on sharia and knowing firsthand how the resolution of problems that arise in a live effort.